The Role of the Judge in Non-Class Settlements - Howard M. Erichson (Washington University Law Review, 2013)
What is the role of the judge in aggregate litigation? That was the question posed to Judge Alvin Hellerstein and several panelists, including myself, at the 2012 Symposium of the Institute of Law and Economic Policy. Judge Hellerstein, who has overseen the litigation arising out of both the September 11 terrorist attacks and the subsequent rescue efforts and clean-up, framed the question more provocatively and purposively: “How do you bring justice to ten thousand cases?” The justice that Judge Hellerstein brought to ten thousand cases in the September 11 clean-up litigation took the form of a massive settlement. Responders who participated in recovery and debris-removal efforts and who suffered respiratory diseases and other ailments had sued New York City and other defendants, claiming that the city had failed to provide adequate protective gear and supervision. Rather than a class action, this was a mass non-class aggregate settlement. Plaintiffs’ liaison counsel negotiated the deal with New York City after several individual cases had been scheduled for trial but before any case had been tried. The resolution was accomplished on a non-class basis because the court had earlier denied class certification on the grounds that the claims were too individualized for class action treatment. In the denial of class certification and the subsequent accomplishment of a mass non-class settlement, the outcome was typical of the past decade’s major mass tort resolutions. But the signal moment of the September 11 clean-up litigation was not typical at all. In March 2010, Judge Hellerstein “rejected” a settlement that the attorneys had negotiated. He sent the parties back to the bargaining table to make the settlement richer. Sure enough, several months later the lawyers returned with a settlement proposal that increased plaintiffs’ compensation, and this time the judge “approved” it. To many observers, there may be something quite appealing about the court’s intervention. The judge helped World Trade Center responders and clean-up workers obtain greater compensation, and the defendant was willing to pay the higher amount rather than go to trial. What I wonder is where the judge got the power to “approve” or “reject” the settlement. I understand, of course, why a judge might wish he had that power. Overseeing a case gives a judge a strong investment in the outcome as well as a sense of what outcome might be just. But settlement is not adjudication. A settlement is a contract in which a claimant agrees to release a claim in exchange for something offered by the defendant. There are special circumstances that require judicial approval of negotiated resolutions; these circumstances turn settlements into something akin to adjudication. But the September 11 clean-up litigation deal was not a class action settlement. It was not a consent judgment in which the parties sought the court’s ongoing supervision. It was not a settlement by minors or others legally incompetent to make their own decisions. Nor was it a shareholder derivative action or an action in which a receiver had been appointed. Rather, it was a settlement of individual claims, albeit in the context of a complex mass dispute. Judge Hellerstein and his special masters—Professors James Henderson and Aaron Twerski—have described in a detailed law review article the challenges they faced in bringing ten thousand claims to resolution. Their reflections provide an apt occasion for considering the role of the judge in bringing a mass dispute to a negotiated resolution.
Keywords: judge; settlement; non-class aggregate settlement; September 11; Alvin Hellerstein